Quatitative morphological analysis of the venous bed of the common bile duct in postresection portal hypertension - N. Ya. Monastyrska (Kazimierz Wielki University, 2020)
Introduction. Removal of the left and right lateral lobes of the liver in white rats leads to postresection portal hypertension, which is characterized by dilation and plethora of the hepatic portal vein, mesenteric veins, esophageal and gastric veins, veins of the anterior abdominal wall, splenomegaly, ascites. Objective of the research: to study the features of structural reorganization of the venous bed of the common bile duct in postresection portal hypertension morphometrically. Materials of the research and their discussion. The venous bed of the common bile duct was studied by morphometric methods in 32 laboratory white male rats, which were divided into 2 groups: 1-st group included 15 intact animals, 2-nd - 17 rats with postresection portal hypertension, which was modeled by removal of the left and right hepatic lobes. One month after the start of the experiment, rats were euthanized by bloodletting under conditions of thiopental anesthesia. Histological micropreparations were made from the common bile duct, on which the venous bed was mophometrically studied, the outer and inner diameters of veins, wall thickness, height of endotheliocytes, diameter of their nuclei, nuclear-cytoplasmic ratios in these cells, relative volume of damaged endothelial cells were measured. Quantitative indicators were processed statistically. Results of the research and their discussion. Morphometrically it was found  that in postresection portal hypertension the outer and inner diameters of veins of the common bile duct markedly increased, their wall is thinned, the height of endothelial cells, the diameters of their nuclei decreased, the nuclear-cytoplasmic ratios in endotheliocytes were disturbed, the relative volume of damaged endothelial cells increased. Conclusions. Resection of the left and right lateral lobes of the liver in white rats leads to postresection portal hypertension and pronounced remodeling of the venous bed of the common bile duct, which was characterized by increase of outer and inner diameters of veins, thinning of their wall, decrease of height of endotheliocytes and diameters of their nuclei, violation of nuclear-cytoplasmic ratios in endothelial cells, increase of relative volume of damaged endothelial cells.